2021
DOI: 10.1055/s-0041-1727284
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Patients Discharged after COVID-19 Hospitalization

Abstract: Background Venous thromboembolism (VTE) is a frequent complication of COVID-19, so that the importance of adequate in-hospital thromboprophylaxis in patients hospitalized with COVID-19 is well established. However, the incidence of VTE after discharge and whether postdischarge thromboprophylaxis is beneficial and safe are unclear. In this prospective observational single-center study, we report the incidence of VTE 6 weeks after hospitalization and the use of postdischarge thromboprophylaxis. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 30 publications
4
83
0
7
Order By: Relevance
“…A total of 266 articles were obtained using our search strategy. After excluding duplicates and preliminary screening, 96 full-text articles were assessed for eligibility, 87 studies were excluded for not meeting the inclusion criteria and 2 records were identified using other sources, leaving 11 investigations fulfilling the inclusion criteria ( Supplementary File 2 ) [3] , [4] , [5] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 266 articles were obtained using our search strategy. After excluding duplicates and preliminary screening, 96 full-text articles were assessed for eligibility, 87 studies were excluded for not meeting the inclusion criteria and 2 records were identified using other sources, leaving 11 investigations fulfilling the inclusion criteria ( Supplementary File 2 ) [3] , [4] , [5] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 18,949 COVID-19 patients were included in this analysis ( Table 1 ). Only four analyses reported the mean hospitalization length, which was 19.5 days [3] , [4] , [11] . Few investigations reported data regarding the administration of post-discharge prophylactic or therapeutic anticoagulation [3] , [4] , [5] , [10] , [11] , [12] , [14] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At 6 weeks, 32% of ward patients and 42% of ICU patients had elevated D‐dimer levels. 20 In another outpatient cohort study of 175 patients, at 60 days the incidence of arterial events was 0% and venous events 0.71% (1 PE at 9 days post discharge), and no bleedings were reported. 21 Similar rates were also reported from a Chinese study of post‐acute COVID‐19 .…”
Section: Post‐acute Covid ‐19 Hematological Complicationsmentioning
confidence: 94%